Dinamika Koneksi Politik dan Keberagaman Gender TMT dalam Memengaruhi Transparansi Pelaporan Keuangan - Talita Adelia Zahira; Mukhtaruddin Mukhtaruddin (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Financial reporting transparency is a crucial element for economic decision-making, yet its integrity is often influenced by internal governance structures and the external political environment. This study aims to examine and summarize scientific findings regarding the influence of gender diversity in Top Management Teams (TMT) and political connections on financial reporting transparency. Using the Systematic Literature Review (SLR) method, this research analyzes 18 scientific articles published between 2020 and 2026. The review results indicate that gender diversity consistently has a positive impact on the quality of corporate information through improved accrual quality, disclosure of Environmental, Social, and Governance (ESG) performance, and the prevention of fraudulent activities. Conversely, political connections act as a "double-edged sword"; on one hand, they tend to decrease transparency related to tax and earnings management due to agency problems, but on the other hand, they can drive the quality of sustainability reports to maintain public legitimacy, particularly in the context of the Indonesian market. These findings also reveal that excessive political influence potentially weakens the positive impact of gender diversity. This research recommends the need to strengthen female representation on boards and implement stricter auditing mechanisms for politically connected firms.